1983
DOI: 10.1210/endo-112-5-1590
|View full text |Cite
|
Sign up to set email alerts
|

Androgen-Controlled Synthesis of Specific Proteins in the Rat Epididymis*

Abstract: Previous investigations have established the production of specific epididymal proteins (SEP) in the rat which become attached to the sperm surface as these cells pass along the duct. The present study is concerned with the regulation of SEP synthesis by androgens. For this purpose, we determined the concentrations of SEP and protein DE, one of its main components (40%), during sexual maturation, after castration with and without androgen administration, and after ligation of the efferent ductuli in rats. SEP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…Earlier studies have not simultaneously analyzed testicular germ cells and epididymal sperm and have thus not addressed this question. Epididymal sperm of the rat acquire other proteins, such as secreted glycoprotein-2 (SGP-2), from the epididymal fluid [48][49][50][51]; these proteins appear to be secretory products of epididymal epithelial cells. If the acquisition of ot-fucosidase parallels that of other products of the epididymal epithelium, it is possible that protein-sperm interaction is mediated by a common post-translational modification.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have not simultaneously analyzed testicular germ cells and epididymal sperm and have thus not addressed this question. Epididymal sperm of the rat acquire other proteins, such as secreted glycoprotein-2 (SGP-2), from the epididymal fluid [48][49][50][51]; these proteins appear to be secretory products of epididymal epithelial cells. If the acquisition of ot-fucosidase parallels that of other products of the epididymal epithelium, it is possible that protein-sperm interaction is mediated by a common post-translational modification.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent analysis of purified CRISP1 by mass spectrometry using an ESI-ion trap LCQ-Duo mass spectrometer (Thermo Fisher Scientific) revealed that all tryptic peptides within the sample corresponded to CRISP1. Polyclonal antibody anti-CRISP1 (8 mg/ml) was produced by immunization of rabbits with purified CRISP1 as previously described [37].…”
Section: Collection Of Epididymal Fluidsmentioning
confidence: 99%
“…For experiments involving the effect of a polyclonal antibody against rCRISP1 (anti-CRISP1) on fertilization, sperm were incubated for 30 min in the presence or absence of the antibody (7.2 mg/ml) [26], or in the presence of normal rabbit serum or normal rabbit immunoglobulin (IgG; Sigma) prior to the addition of the eggs to the IVF drops. For those cases in which the effect of rCRISP1 on fertilization was examined, eggs were incubated for 30 min in medium alone or in medium containing 6 lM purified rCRISP1 [5,6]; ovalbumin (OA; Sigma); recCRISP1, expressed as a fusion protein coupled to maltose-binding protein (MBP) [14]; or MBP prior to insemination.…”
Section: In Vitro Fertilization (Ivf)mentioning
confidence: 99%